eSalud para adultos mayores: un análisis de la adopción de tecnologías en la prevención y control de enfermedades - García González, Janet (2024)
The research addresses the impact of Information and Communication Technologies (ICT) on the well-being of older adults. The problem lies in the lack of digital skills and distrust in technology, which limits its adoption and potential benefits in disease prevention and control. The objective is to determine how the use of ICT influences active aging and disease prevention. A qualitative methodology with an exploratory approach was used, based on focus groups of older adults in Xalapa, Veracruz. Mexico. The results show that, although ICT can improve the quality of life by facilitating communication and access to services, there are challenges such as lack of digital skills and distrust in technology. The conclusions highlight the need for inclusive policies and training to maximize the benefits of ICT in this population group